Morphology of titanium nanofilms onto sapphire at annealing in vacuum - Durov, O.V.; Stetsyuk, T.V. (Physics and Chemistry of Solid State, 2025)
A change in the morphology of titanium films on the surface of sapphire was investigated when heated in a vacuum. The coatings interact with the substrate, forming two phases with different adhesion to sapphire. Probably the phase with low adhesion is an intermetallides of the titаnium-aluminum system, and the phase with high adhesion is titanium oxide.